Analisis Drugs Related Problems pada Pasien Kanker Payudara di Rumah Sakit Umum Daerah KRMT Wongsonegoro Semarang Tahun 2022 - Sri Susilowati; Firda Shely Septasari (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2024)
Drugs Related Problems (DRPs) are problems related to patient treatment that can affect the effectiveness and safety of therapy. Breast cancer patients who receive chemotherapy usually consists of a combination of several drugs. Administration of a combination of chemotherapy drugs can cause DRPs. This study aims to determine the actual and potential incidence of DRPs and their causes in breast cancer patients at the KRMT Wongsonegoro Regional General Hospital, Semarang in 2022. This research was conducted observationally with a cross-sectional research design and retrospective data collection by observing medical record data of breast cancer patients. There were 30 samples that met the inclusion and exclusion criteria. The classification of DRPs refers to the Regulation of the Minister of Health of the Republic of Indonesia Number 34 of 2021 concerning Standards of Pharmaceutical Services in Clinics. DRPs were analyzed using the National Guidelines for Medical Services for Breast Cancer Management in 2018. Analysis of potential drug interactions used medscape.com. Data analysis was carried out descriptively. The results showed that the most frequently used chemotherapy regimen was cyclophosphamide + doxorubicin + fluorouracil (76.67%). All patient samples experienced actual and potential DRPs with the cause being indication without medication (46.67%), medication without indication (0%), too high a dose (90%), too low a dose (100%), side effects undesired (100%), potential drug interactions (100%) and duration of treatment (53.2%). The prevalence of DRPs in our setting was high so that it could affect therapy outcomes of patient. Therefore, it is hoped that there will be an evaluation to reduce the prevalence of DRPs, by optimizing clinical pharmacy service practices such as reviewing prescriptions, monitoring effectiveness therapy and adverse drug reaction also conducting interprofessional collaboration.